2005
DOI: 10.1111/j.1365-2796.2005.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin and vitamin E on lipoproteins and oxidative stress in dialysis patients: a randomised‐controlled trial

Abstract: Abstract. Diepeveen SHA, Verhoeven GWHE, van der Palen J, Dikkeschei LD, van Tits LJ, Kolsters G, Offerman JJG, Bilo HJG, Stalenhoef AFH (Isala Clinics, location Weezenlanden, Zwolle; Medical Spectrum Twente, Enschede; and Radboud University Nijmegen Medical Center, Nijmegen, the Netherlands). Effects of atorvastatin and vitamin E on lipoproteins and oxidative stress in dialysis patients: a randomised-controlled trial. Objectives. The objective of this study was to examine the effects of treatment with atorvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 27 publications
1
43
0
1
Order By: Relevance
“…Anti-oxidative and anti-inflammatory actions are also major pleiotropic effects of statins (12). Several reports have shown that these actions of statins contribute to their renoprotective effects (5,30,31). In the present study, we also observed that pravastatin and rosuvastatin suppressed oxidative stress in db/db mice as well as these reports, whereas we could not detect the anti-inflammatory effect of statins in the kidneys of db/db mice.…”
Section: Discussionsupporting
confidence: 66%
“…Anti-oxidative and anti-inflammatory actions are also major pleiotropic effects of statins (12). Several reports have shown that these actions of statins contribute to their renoprotective effects (5,30,31). In the present study, we also observed that pravastatin and rosuvastatin suppressed oxidative stress in db/db mice as well as these reports, whereas we could not detect the anti-inflammatory effect of statins in the kidneys of db/db mice.…”
Section: Discussionsupporting
confidence: 66%
“…Although the SPACE study did not systematically measure levels of oxidative stress biomarkers in response to therapy, two subsequent reports have not found a significant effect of administering a-tocopherol, 800 IU/d, on plasma oxidized LDL or oxidative protein product concentration. 51,52 Similar to the SPACE study, a randomized trial comparing the antioxidant N-acetyl cysteine with placebo in dialysis Changes in F2 isoprostanes from baseline at month 6. Levels stayed relatively stable throughout the study for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients treated with statins to reduce LDL cholesterol levels, interactions with simultaneously ingested vitamin E supplements may occur. A combined treatment with atorvastatin and α-TOH in stable, non-diabetic dialysis patients revealed a reduced in vitro oxidizability of LDL [241] . Podszun et al [242] found no interactions in guinea pigs fed with high-dose α-TOH (250 mg/kg diet)…”
Section: Interactions With Pharmaceuticsmentioning
confidence: 95%
“…The results depend, among others, on the evaluation of the data. When vitamin E serum levels were measured without any corrections most researchers found a decrease [241,[246][247][248][249][250] ; however, when vitamin E serum levels were normalized to plasma lipids, such as LDL cholesterol, total serum cholesterol or serum triglycerides, increased or unchanged ratios of vitamin E and serum lipids were observed [247,[249][250][251][252] . The underlying processes are still unclear but on the one hand, the decrease of circulating lipoproteins could directly cause reduced levels of vitamin E (in terms of absolute concentrations), whereas the ratio of vitamin E to serum lipids could at the same time be increased, as statins mostly decrease specific lipid fractions, namely LDL cholesterol and total cholesterol.…”
Section: Interactions With Pharmaceuticsmentioning
confidence: 97%